The Meanings, The Associations, and The Functions of Metaphors in Sports Discourse in Kompas Newspaper - Devi Melisa Saragi (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2020)
ABSTRACTThis research describes the semantic features of metaphors found in sports discourse in Kompas daily newspaper using semantic decomposition, contrasting the semantic components of the source language and the metaphorical expression to discover the meaning, the similar association, and the functions of the metaphors written in the course. Nonparticipant observation, critical reading, and note-taking were used to collect the data. Then all the data was analyzed by using referential identity and distributional methods with substitution and paraphrasing techniques. The first result of this research showed that each fundamental element elaborated by analyzing each domain's diagnostic components could explain the association between the source language and the metaphor. The second result is that the text's association included four similarities; attributes, movement, qualities, and action. The third conclusion is that the metaphors' functions explain and decribe the situation, entertain the team, and evaluate the team. Keyword; metaphors, semantic feature, semantic decomposition, newspaper.